A Reliability Evaluation of High Speed Railway Traction Substation Based on the GO-FLOW Methodology - Li Liang; Feng Zhao; Sihua Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to assure the uninterrupted power supply of high speed railway, the reliability assessment of traction substation is essential at the design stage. Based on the system reliability engineering theory, a new system reliability analysis method called the GO-FLOW methodology is applied in the reliability assessment of traction substation of high speed railway. Considering failure and dynamic characteristics over time of the components and shutdown correlation of electrical equipments in substation, on the analysis of the traction power supply system, the GO-FLOW chart of traction power supply system is established by taking the uninterrupted power supply as its target. Their operators signal flows and operation rules are analyzed. Then, the quantitative and qualitative assessment of reliability are realized, the weakness of system is determined. Thus, the reliability evaluation of high-speed railway traction power supply system is completed.